1997
DOI: 10.1139/e17-032
|View full text |Cite
|
Sign up to set email alerts
|

Partition coefficients for Ni, Cu, Pd, Pt, Rh, and Ir between monosulfide solid solution and sulfide liquid and the formation of compositionally zoned Ni – Cu sulfide bodies by fractional crystallization of sulfide liquid

Abstract: Many nickel–copper sulfide orebodies contain Cu- and Fe-rich portions. The Fe-rich ore is generally richer in Os, Ir, Ru, and Rh and poorer in Pt, Pd, and Au than the Cu-rich ore. In komatiite-hosted ores Ni tends to be concentrated in the Cu-rich ore, whereas in tholeiitic ores it tends to be concentrated in the Fe-rich ore. The origin of this zonation could be due to crystal fractionation of Fe-rich monosulfide solid solution from a sulfide liquid. The crystal fractionation would produce an Fe-rich cumulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(38 citation statements)
references
References 15 publications
2
34
0
2
Order By: Relevance
“…The partition coefficients for Cu and Ni shown in Table 2 are similar to previously published data for the oxygen-free system Fe-Ni-Cu-S (e.g., Barnes et al, 1997). This is not surprising, in light of the exceedingly low O contents of Ni-and Cu-bearing liquids in our experiments even at f O 2 as high as QFM.…”
Section: Base Metal Partitioningsupporting
confidence: 91%
See 2 more Smart Citations
“…The partition coefficients for Cu and Ni shown in Table 2 are similar to previously published data for the oxygen-free system Fe-Ni-Cu-S (e.g., Barnes et al, 1997). This is not surprising, in light of the exceedingly low O contents of Ni-and Cu-bearing liquids in our experiments even at f O 2 as high as QFM.…”
Section: Base Metal Partitioningsupporting
confidence: 91%
“…At high f O 2 (QFM) and high f S 2 (Pt-PtS), D Ni is much higher, and shows a moderate increase with decreasing temperature to reach a maximum of 0.90 at 950°C. It is likely that at slightly higher f S 2 or slightly lower temperature Ni would become compatible in mss, as has been shown in the oxygen-free system (e.g., Barnes et al, 1997).…”
Section: Base Metal Partitioningmentioning
confidence: 73%
See 1 more Smart Citation
“…The results for Ni and Cu were reported in Li et al (1996) and Barnes et al (1997b, Figure 2). In these papers it was shown that D mss/liq in the S-Fe-Ni-Cu-PGE system are similar to the values reported by Fleet and Pan (1994) and Ebel and Naldrett (1997) for the S-Fe-NiCu system.…”
Section: Nickel and Coppermentioning
confidence: 79%
“…These partition coefficients are important since they are used in models of a number of processes. The partitioning of metals between sulphide liquid and monosulphide solid solution (mss) could explain the compositional zonation Proton microprobe results for the partitioning of platinum-group elements between monosulphide solid solution and sulphide liquid observed in many magmatic sulphide ores (Barnes et al, 1997b and references therein). Bulanova et al (1996) have used D mss/liq to interpret the OsIrRu-enriched patterns they found in a sulphide inclusion in a kimberlite diamond.…”
Section: Introductionmentioning
confidence: 99%